Parenting Self-Efficacy as a Mediator Between Social Support and Homeschooling Mothers’ Well-being - Lydiawaty, Maria Goretty (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Homeschooling mothers often encounter unique psychological and practical challenges in fulfilling their dual roles as caregivers and educators. Social support is believed to be a crucial factor influencing their subjective well-being, which includes life satisfaction, positive affect, and negative affect. This study aimed to examine the mediating role of parenting self-efficacy in the relationship between social support and the subjective well-being of homeschooling mothers affiliated with Komunitas X in Jakarta and PKBM Y in Bandung. Using a quantitative, correlational design, the research involved a total of 114 homeschooling mothers who were selected through purposive sampling from Komunitas X in Jakarta and PKBM Y in Bandung. Participants completed validated self-report instruments measuring perceived social support, parenting self-efficacy, life satisfaction, positive affect and negative affect. Data were analyzed using Hayes’s PROCESS macro in SPSS version 25 to examine indirect effects. The results showed that social support significantly predicted parenting self-efficacy (b = 0.41, p <.001), which subsequently predicted life satisfaction (b = 0.11, p <.001), positive affect (b = 0.14, p <.001) and negative affect (b = -0.15, p <.001). Social support also had direct effects on all three well-being components. Indirect effects were significant for life satisfaction (b = 0.04; 95% CI [0.0138, 0.0962]), positive affect (b = 0.06; 95% CI [0.0194, 0.1170]), and negative affect (b = -0.06; 95% CI [-0.1312, -0.0205]), indicating partial mediation. These findings underscore the critical role of parenting self-efficacy in enhancing the benefits of social support. Interventions aimed at promoting parenting confidence and strengthening support networks could improve the overall well-being of homeschooling mothers.Ibu yang menjalani homeschooling sering menghadapi tantangan psikologis dan praktis yang unik dalam memenuhi peran ganda mereka sebagai pengasuh dan pendidik. Dukungan sosial diyakini sebagai faktor penting yang memengaruhi kesejahteraan subjektif mereka, yang mencakup kepuasan hidup, afek positif, dan afek negatif. Penelitian ini bertujuan untuk menguji peran mediasi dari efikasi diri dalam pengasuhan terhadap hubungan antara dukungan sosial dan kesejahteraan pada ibu-ibu homeschooling yang tergabung di Komunitas X di Jakarta dan PKBM Y di Bandung. Dengan menggunakan desain kuantitatif korelasional, penelitian ini melibatkan total 114 ibu homeschooling yang dipilih melalui teknik purposive sampling dari Komunitas X di Jakarta dan PKBM Y di Bandung. Partisipan mengisi instrumen laporan diri terstandarisasi yang mengukur persepsi dukungan sosial, efikasi diri pengasuhan, kepuasan hidup, afek positif, dan afek negatif. Data dianalisis menggunakan Hayes’s PROCESS macro dalam SPSS versi 25 untuk menguji efek tidak langsung. Hasil menunjukkan bahwa dukungan sosial secara signifikan memprediksi efikasi diri pengasuhan (b = 0.41, p <.001), yang kemudian memprediksi kepuasan hidup (b = 0.11, p <.001), afek positif (b = 0.14, p <.001), dan afek negatif (b = -0.15, p <.001). Dukungan sosial juga memiliki efek langsung terhadap ketiga komponen kesejahteraan. Efek tidak langsung juga signifikan untuk kepuasan hidup (b = 0.04; 95% CI [0.0138, 0.0962]), afek positif (b = 0.06; 95% CI [0.0194, 0.1170]), dan afek negatif (b = -0.06; 95% CI [-0.1312, -0.0205]), yang menunjukkan adanya mediasi parsial. Temuan ini menekankan pentingnya efikasi diri pengasuhan dalam meningkatkan manfaat dukungan sosial. Intervensi yang bertujuan untuk meningkatkan kepercayaan diri dalam mengasuh dan memperkuat jaringan dukungan dapat meningkatkan kesejahteraan ibu homeschooling secara keseluruhan.